2019
DOI: 10.1007/s11682-019-00086-8
|View full text |Cite
|
Sign up to set email alerts
|

White matter disconnection is related to age-related phonological deficits

Abstract: Older adults have more language production difficulties than younger adults but display largely comparable language comprehension abilities. The Transmission Deficit Hypothesis suggests that production difficulties stem from an age-related increase in phonological signal transmission failures, while the semantic system, being more redundant than the phonological system, allows comprehension to be relatively preserved despite signal failures. Though the neural instantiation of the Transmission Deficit Hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 60 publications
2
17
1
Order By: Relevance
“…Our analysis revealed that mean age moderated the FA-naming correlation of the left superior longitudinal fasciculus and sex influenced the correlation with comprehension. Similar results were reported by recent studies showing that age attenuated the FA-naming association of dorsal tracts (Troutman & Diaz, 2019) and that there were sex differences in FA-comprehension correlations (Jung et al, 2019). However, these statistical findings should be interpreted with caution, considering the underlying neural mechanism remains uncertain.…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis revealed that mean age moderated the FA-naming correlation of the left superior longitudinal fasciculus and sex influenced the correlation with comprehension. Similar results were reported by recent studies showing that age attenuated the FA-naming association of dorsal tracts (Troutman & Diaz, 2019) and that there were sex differences in FA-comprehension correlations (Jung et al, 2019). However, these statistical findings should be interpreted with caution, considering the underlying neural mechanism remains uncertain.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the significant increase in RD on the ACR signifies an age-related demyelination effect of that tract, based on previous animal and human studies investigating RD and its relationship to neural networks ( Song et al, 2002 , 2003 , 2005 ; Nair et al, 2005 ; Budde et al, 2007 ), as well as evidence supporting typical aging is accompanied by myelin damage and loss ( Peters, 2002 ). Our study did not find any association between ACR and VF, but Troutman and Diaz (2020) observed that higher RD across dorsal, ventral, and fronto-striatal tracts was associated with poorer performance on a naming with distractors task, suggesting that demyelination can result in poorer language performance.…”
Section: Discussioncontrasting
confidence: 91%
“… Houston et al (2019) reported the performance on a word-retrieval task was associated with increased FA within the inferior fronto-occipital fasciculus (IFOF), in addition to the SLF, and observed increased FA within the corpus callosum that was associated with lower VF scores. Troutman and Diaz (2020) observed among all adult age groups that better performance on a naming with distractors task was associated with lower RD across dorsal, ventral, and fronto-striatal tracts as well as higher FA along dorsal tracts but was unable to find an association when covarying for age groups. Teubner-Rhodes et al (2016) looked at age-related performance in acquisition and retrieval of lexical and semantic information and found age-related declines in arcuate fasciculus (AF) microstructure were related to cognitive processing speed, but not to vocabulary retrieval.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…These tracts include the superior longitudinal fasciculus-III (Houston et al, 2019;SLF, White Matter Mediation in Picture Naming, page 5 Madhavan et al, 2014;Stamatakis et al, 2011;Troutman & Diaz, 2019), the inferior longitudinal fasciculus (ILF, Kantarci et al, 2011;Stamatakis et al, 2011;Troutman & Diaz, 2019), and the frontal aslant tract (FAT, Catani et al, 2013;Rizio & Diaz, 2016;Troutman & Diaz, 2019). It is important to note that there are several models of these tracts (for reviews, see Dick et al, 2014;Dick & Tremblay, 2012;Friederici, 2009Friederici, , 2012Varriano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%